PREDICTION OF SOIL SETTLEMENT ON SOFT CLAY SOIL USING NORMALIZED ROTATIONAL MULTIPLE YIELD SURFACE FRAMEWORK (NRMYSF) (Jurnal Teknologi (Sciences & Engineering), 2022)
Soft clays are highly compressible, high-water content, low shear strength, and have poor permeability, which result in significant settlement under long-term loads. Therefore, one of the most challenging geotechnical engineering problems is to predict the settlement from soft clay soil. Normalized Rotational Multiple Yield Surface Framework (NRMYSF) is developed from the soil stress-strain behaviour and shear strength characteristic. It is able to estimate the stress-strain curve for shear strength in triaxial tests. The consolidated drained (CD) triaxial tests and conventional 1-dimensional consolidation of oedometer has been conducted on soft clay soil. The settlement soil prediction was compared between the NRMYSF and conventional 1-dimensional consolidation under Terzaghi’s principle. The NRMYSF prediction model was smaller than the conventional oedometer by 0.1459m to 0.1431m for Sample A, and by 0.1890m to 0.1398m for Sample B. Therefore, this method has the potential to predict the settlement of soft clay soils.